Technologies for the study of hydropeaking impacts on fish populations: Applications, advantages, outcomes, and future developments. (13th August 2022) - Alexandre, Carlos M.; Quintella, Bernardo R.; Ovidio, Michaël; Boavida, Isabel; Costa, Maria J.; Palstra, Arjan P.; de Lima, Rui L. Pedroso; de Lima, Maria Isabel P.; de Lima, João L.M.P.; Almeida, Pedro R.
Abstract: Dam construction and streamflow regulation are increasing throughout the world, with impacts in impounded aquatic ecosystems. Hydropower dams, some of them causing a phenomenon called "hydropeaking" during their operation, are known for having a variety of impacts on downstream aquatic biota, particularly fish, and respective habitat. This can result in significant changes, from the community (e.g., fish assemblage structure) to the individual level (e.g., physiological and behavioural adjustments). Researchers and managers involved in the assessment of hydropeaking impacts must be resourceful and use methods that allow their precise evaluation, from large to fine‐scale habitat and biological responses. In the last decades, technological advances allowed for the development of techniques and instrumentations that are increasingly being used in hydropeaking impact and mitigation assessments. This paper aims to provide a review, to researchers and managers interested in this field, of some of the most innovative methods and techniques, involving technology, that are available to study hydropeaking effects on downstream ecosystem, particularly from a fish perspective. We discuss the fundamentals behind such techniques, their advantages, and disadvantages, while also providing practical examples of their application and of the type of results that can be obtained. We finish by discussing some of the shortcomings of these methods and how related technology can evolve to solve current limitations.